2001
DOI: 10.1103/physrevd.63.094006
|View full text |Cite
|
Sign up to set email alerts
|

Nonrelativistic QCD analysis of bottomonium production at the Fermilab Tevatron

Abstract: Recent data from the CDF collaboration on the production of spin-triplet bottomonium states at the Tevatron pp collider are analyzed within the NRQCD factorization formalism. The color-singlet matrix elements are determined from electromagnetic decays and from potential models. The color-octet matrix elements are determined by fitting the CDF data on the cross sections for Υ(1S), Υ(2S), and Υ(3S) at large p T and the fractions of Υ(1S) coming from χ b (1P ) and χ b (2P ). We use the resulting matrix elements t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(176 citation statements)
references
References 30 publications
8
168
0
Order By: Relevance
“…We take the mass of the charm quark, m charm = 1.4GeV [16]. The values of the color-singlet operators for bottomonia are given in [15], which we reproduce here:…”
Section: Matrix Elements For Quarkonia Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…We take the mass of the charm quark, m charm = 1.4GeV [16]. The values of the color-singlet operators for bottomonia are given in [15], which we reproduce here:…”
Section: Matrix Elements For Quarkonia Productionmentioning
confidence: 99%
“…Since these are short distance operators, they can be calculated in perturbation theory. We use the expressions for the short distance color-singlet cross sections given in [47,48] and the color-octet cross sections given in [13][14][15]. The case of the p-wave bound states (χ c0 , χ c1 , and χ c2 , sometimes collectively referred to as χ cJ , and the corresponding states of the b quark) is slightly different.…”
Section: A Nrqcd Calculation Of Dσ/dtmentioning
confidence: 99%
See 1 more Smart Citation
“…The product of acceptance and efficiency for detecting J/ψ decay to µ + µ − is estimated to be ǫ ≈ 0.1 [16], which is perhaps a conservative estimate for LHC. Multiplying the number of the produced events by ǫ 2 , we expect between 1 and 10 observed events per year.…”
Section: Observation Potential Of η B → J/ψ J/ψ At Tevatron and Lhcmentioning
confidence: 99%
“…Encouraged by the large observed width of η c → V V (V stands for light vector mesons), Braaten, Fleming and Leibovich (hereafter BFL) have suggested that the analogous decay process η b → J/ψJ/ψ, followed by both J/ψ decays to muon pairs, may be used as a very clean trigger to search for η b at Tevatron Run 2 [16]. Assuming Br[η b → J/ψJ/ψ] ∼ 1/m 4 b , they rescale the measured branching ratio of η c → φφ by a factor of (m c /m b ) 4 to estimate 1 Br[η b → J/ψJ/ψ] = 7 × 10 −4±1 .…”
Section: Introductionmentioning
confidence: 99%